1993
DOI: 10.1192/s0007125000292192
|View full text |Cite
|
Sign up to set email alerts
|

The TAPS Project. 7: Mental Hospital Closure - A Literature Review of Outcome Studies and Evaluative Techniques

Abstract: Various techniques have been used to assess the results of ‘deinstitutionalisation’. This paper reviews these outcome studies, most of which have concluded that a new long-stay group will replace the old long-stay patients, and that a residual group of ageing patients, mostly with organic syndromes, is difficult to accommodate in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 62 publications
1
23
0
2
Order By: Relevance
“…This result fits with original suggestions that NC residents come t o live in National Health Service (NHS)-funded facilities because of their difficulties finding appropriate placements within the community (Bollini et al, 1986;O'Driscoll, 1993). On the other hand, this difference could also be a factor of the type of care provided, such that the social difficulties in NC were a product of the NC environment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result fits with original suggestions that NC residents come t o live in National Health Service (NHS)-funded facilities because of their difficulties finding appropriate placements within the community (Bollini et al, 1986;O'Driscoll, 1993). On the other hand, this difference could also be a factor of the type of care provided, such that the social difficulties in NC were a product of the NC environment.…”
Section: Discussionsupporting
confidence: 85%
“…There is a common view that nursing care (NC) settings provide care for a select group of highly dependent elderly, who because of their special medical and/or psychiatric needs, have proven to be difficult to place elsewhere (Bollini et al, 1986;O'Driscoll, 1993). These people with special needs include many individuals with dementia, a mental illness that involves a complex mix of psychological, social, and physical changes that many community and residential services find difficult to manage (Aronson et al, 1992;Chester & Bender, 1999).…”
mentioning
confidence: 95%
“…Notwithstanding the magnitude of this development, many studies have investigated small samples of residents and used a cross-sectional design [3][4][5]. Only a few longitudinal studies have yielded important information about this population, consistently indicating the difficulties involved in discharging and placing these patients in independent accommodations [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the variability in study design and the wide diversity of research focus make it unlikely that a more systematic review would yield much in the way of definitive evidence to support one model of supported housing over another. Only one systematic review (Quilgars, 2000) of low intensity support services and two relevant literature reviews (O'Driscoll, 1993;Thornicroft & Bebbington, 1989) were found during the search process. Consequently this review should be seen as a preliminary attempt to provide an overview of existing literature that identifies areas where more research might be required in future.…”
Section: Search Strategymentioning
confidence: 99%